Out of mind, out of sight? Investigating abnormal face scanning in autism spectrum disorder using gaze‐contingent paradigm. Issue 1 (28th June 2019) - Wang, Qiandong; Hoi, Sio Pan; Wang, Yuyin; Song, Ci; Li, Tianbi; Lam, Cheuk Man; Fang, Fang; Yi, Li
Abstract: Diminished social motivation is hypothesized to explain abnormal face scanning pattern in individuals with autism spectrum disorder (ASD), especially reduced eye‐looking time in ASDs than typically developing (TD) people. Here, we tested an alternative explanation that children with ASD may use a compensatory strategy to avoid direct eye contact by processing the eyes through peripheral vision. We compared the face scanning patterns of children with and without ASD in two conditions: in the clear condition, the face was completely visible; in the blur condition, by using the gaze‐contingent paradigm, the whole face was blurred except for a small region being fixated at, thus children could not rely on the peripheral information to process the eyes. We found that children with ASD fixated less on the eyes than TD children in both conditions. Temporal‐course analyses further revealed the possible motivation‐based guidance of attention to process the eyes in the TD group but not in the ASD group. Additionally, we found that children with ASD scanned faces more randomly and less strategically than TD children. These results have ruled out the alternative hypothesis that the abnormal face scanning pattern in ASDs was due to their compensatory strategy to process eyes through peripheral vision, furthering our understanding of the mechanisms underlying their abnormal face scanning. Abstract : We tested whether children with Autism Spectrum Disorder (ASD) might use a compensatory strategy to avoid direct eye contact by processing eyes through peripheral vision. By using the gaze‐contingent paradigm, we blurred the whole face except for a small region being fixated at, thus children could not rely on the peripheral information to process eyes. We found that children with ASD still looked less at eyes than typically developing (TD) children when scanning blurred faces. Temporal‐course analyses further revealed the possible motivation‐based guidance of attention to process eyes in the TD group but not in the ASD group. Our results rule out the hypothesis that children with ASD use a compensatory strategy to process eyes through peripheral vision.